Analysis of Tissues Following Mesenchymal Stromal Cell Therapy in Humans Indicates Limited Long‐Term Engraftment and No Ectopic Tissue Formation123. (18th June 2012) - von Bahr, L.; Batsis, I.; Moll, G.; Hägg, M.; Szakos, A.; Sundberg, B.; Uzunel, M.; Ringden, O.; Le Blanc, K.
Abstract: Mesenchymal stromal cells (MSCs) are explored as a novel treatment for a variety of medical conditions. Their fate after infusion is unclear, and long‐term safety regarding malignant transformation and ectopic tissue formation has not been addressed in patients. We examined autopsy material from 18 patients who had received human leukocyte antigen (HLA)‐mismatched MSCs, and 108 tissue samples from 15 patients were examined by PCR. No signs of ectopic tissue formation or malignant tumors of MSC‐donor origin were found on macroscopic or histological examination. MSC donor DNA was detected in one or several tissues including lungs, lymph nodes, and intestine in eight patients at levels from 1/100 to <1/1, 000. Detection of MSC donor DNA was negatively correlated with time from infusion to sample collection, as DNA was detected from nine of 13 MSC infusions given within 50 days before sampling but from only two of eight infusions given earlier. There was no correlation between MSC engraftment and treatment response. We conclude that MSCs appear to mediate their function through a "hit and run" mechanism. The lack of sustained engraftment limits the long‐term risks of MSC therapy. STEM CELLS 2012;30:1575–1578